Reservoirs Geothermal Prediction and Potentiality of Power Generation Utilizing Brine Characterizations Produced in Oil Fields - Ibrahim M. Abou El Leil; Seham N. Tawfic; Abdel Moneam Hassn (African Journal of Advanced Pure and Applied Sciences, 2024)
Geothermal is heat energy that is naturally formed below the ground surface. It is one of the important source of renewable energies which is expected to be able to produce electrical power as an alternative of fossil fuels in the future. Reservoir temperature research is fundamental initial research to explore the origin of fluids and reservoir temperature estimation to determine the potential sources of geothermal from surface manifestations. This study is aiming highlights the potentiality of utilization the chemical characterizations such as cations concentrations in produced water (Brine) in oil wells to predict reservoir temperature because of the degree of water temperature is main parameter to determine and classify the geothermal reservoir e.g. law, medium or high enthalpy. Whereas, one of the key uses of geothermal energy is electric-power generation using three basic types of geothermal power plants: dry steam, flash steam, and binary. Twelve producing oil wells in Jailo oilfield were selected for temperature estimation study of the geothermal reservoir has been carried out using geothermometer equations for temperature calculations involving the concentrations of Na+, K+, Ca++, and SiO2. The obtained results revealed that the geothermal classification of reservoirs according to the published references using enthalpy type there are a different enthalpies and the geothermal of reservoir can be classified into Ultra low enthalpy, very low enthalpy, medium enthalpy and high enthalpy. Consequently of these classification the potentiality of electric power generation varies according the geothermal temperature degree and the power plant system. Generally it could be in the current time and with the application of current technology, geothermal energy generator electricity power plant can be applied and the geothermal temperature can be applied for direct and indirect geothermal applications.